Re-reading the myth of medusa in ecological crisis - Muhammad Fuad Hasyim (Life and Death: Journal of Eschatology, 2026)
Background: This paper reinterprets the myth of Medusa in the context of ecological crisis. By exploring the relationship between myth, the unconscious, the oppression of women, and nature, this paper attempts to reveal how hierarchical structures of domination shape the human perspective in understanding nature as an object. Methods: This study adopts a qualitative interpretative approach using symbolic hermeneutics grounded in Carl Jung’s concept of the collective unconscious and Hélène Cixous’ feminist deconstruction. Jung’s framework is used to read Medusa as an archetypal symbol of repressed fear and human–nature relations, while Cixous’ perspective critically reinterprets the myth to expose patriarchal narratives and reconstruct Medusa as a metaphor for liberation and ecological consciousness. Findings: This paper asserts that the root of the oppression and exploitation of nature lies in the binary logic that separates humans and nature. The human narrative of nature is also a narrative of domination, in which the distance between humans and nature is constantly maintained. Humans construct the "shortest distance" through an awareness of duality, distinguishing themselves from nature while remaining connected and dependent, and the "longest distance" through an awareness of an entity that places itself outside and above nature. As a result, humans become alienated from nature and lose the ability to listen to its voice. Conclusion: This paper concludes that restoring the position of nature and humans requires reclaiming the language of nature, which has been usurped by technology and the scientific revolution. A new ecological consciousness must arise from the recognition that humans are not the only subjects in power, but rather part of an interconnected web of life. Novelty/Originality of this article: Medusa's petrifying gaze and the nature gaze that awakens consciousness become reflective metaphors, suggesting that it is not only humans who are capable of conquering; nature can also "gaze back" through disasters, famine, drought, and death.